Selenoproteins and oxidative stress-induced inflammatory tumorigenesis in the gut - Barrett, Caitlyn W. (Cell Mol Life Sci, 2016)
Selenium is an essential micronutrient that is incorporated into at least 25 selenoproteins encoded by the human genome, many of which serve antioxidant functions. Because patients with inflammatory bowel disease (IBD) demonstrate nutritional deficiencies and are at increased risk for colon cancer due to heightened inflammation and oxidative stress, selenoprotein dysfunction may contribute to disease progression. Over the years, numerous studies have analyzed the effects of selenoprotein loss and shown that they are important mediators of intestinal inflammation and carcinogenesis. In particular, recent work has focused on the role of selenoprotein P (SEPP1), a major selenium transport protein which also has endogenous antioxidant function. These experiments determined SEPP1 loss altered immune and epithelial cellular function in a murine model of colitis-associated carcinoma. Here, we discuss the current knowledge of SEPP1 and selenoprotein function in the setting of IBD, colitis, and inflammatory tumorigenesis.